Sustainability assessment of electronic waste remanufacturing: the case of laptop - Atescan Yuksek, Yagmur; Haddad, Yousef; Pagone, Emanuele; Jagtap, Sandeep; Haskew, Steve; Salonitis, Konstantinos (Elsevier, 2023)
Over the years, electronic waste accumulation has been on a steep rise, parallel with the technological evolution of electrical and electronic equipment. Companies have adopted circular economy approach to overcome the emerging waste issue in the last few decades, where goods can return to manufacturers or remanufacturers. They can be used after certain modifications or remanufacturing processes. The remanufacturing of a laptop refers to the disassembly, inspection, part repair, and upgrade of the original laptop to give it a new life, along with a warranty that it is as good as a new product. The goal of this study includes studying and evaluating the total environmental impact of remanufacturing operations of a laptop conducted by a remanufacturing company using Life Cycle Assessment. The system boundaries include all the operations of the remanufacturing company, starting with collecting discarded laptops and ending with distributing remanufactured laptops. The results show that transportation, with maximum contribution from air transportation, has the highest CO2eq emission due to the centralized remanufacturing operations of the company. It is also proven that remanufacturing a laptop has a much smaller environmental impact than a newly manufactured laptop.
Keywords: remanufacturing; e-waste; life cycle assessment; sustainability